OPTOELECTRONIC HELIOTRANSFORMER OF ENERGY - Khomidov, A.K.; Akhunov , K.Kh. (Educational Research in Universal Sciences, 2023)
The article gives descriptions about a solar device for generating electric fields by means of a concentrated beam. The device is a multistage transformer with an optical input. A structural block diagram and the principle of operation of an optoelectronic solar energy transformer are given.